Hierarchical Polymeric Nanocomposite for Water Remediation: Electrospun Nanofibers of a Poly (Ionic Liquid) and tio2 Nanoparticles for Adsorption and Photocatalytic Removal of Rhodamine B - Cordoba-Manrique, A (ELSEVIER, 2025)
Herein we proposed a novel material that consisted in an electrospun nanocomposite made by the combination of TiO2 NPs embedded over a mat of nanofibers composed by a polymer blend of poly (vinyl pyrrolidone) (PVP) and a poly(ionic liquid) (PIL) obtained by electrospinning process. The PIL consisted of positively charged N-ethylated poly(vinylimidazole) anchored with a bis(trifluoromethylsulfonyl imide) (NTf2-) counterion. Polymers and materials were characterized by several experimental techniques, as well as the interaction between the components (polymers and inorganic NPs), which was also sustained by computational tools. The processing protocol for the electrospinning enabled the obtention of PILs as nanofibers with average diameters below 500 nm in all cases, process that was optimized in terms of applied voltage and PIL concentration in the polymer solution by a design of experiment (DOE) approach of 2 factors and 3 levels. The use of DOE allowed the obtention of appropriate experimental conditions to minimize nanofibers diameter to 93 nm also with an adequate dispersion of the same. The nanocomposite made from TiO2 NPs supported on PVP-PIL nanofibers demonstrated excellent capability to adsorb anionic pollutants like Rhodamine B (RhB), revealing an adsorption capacity of 41 mg/g with a kinetic of pseudo first order, suggesting that electrostatic interactions of cationic PILs with the anionic dye, are the main driven force for the adsorption process. Model experiment demonstrated that this system was capable of removing almost 61.0 % of RhB molecules from aqueous solutions. Additionally, TiO2 NPs within the nanofibers allowed to further remove RhB from the aqueous solutions using UV irradiation to degrade the pollutant in an additional 10.2 % of dye removal.